KONTRIBUSI KELINCAHAN DAN KECEPATAN TERHADAP KEMAMPUAN DRIBBLING ATLET SEPAKBOLA SSB SKB MUARA BUNGO - ikhsanmaulana putra; Deka Ismi Mori Saputra (LP3M Universitas Muhammadiyah Muara Bungo, 2019)
The problem in this study is the low ability of dribbling for SSB football layers in Muara Bungo Learning Activity Studio, which is allegedly due to lack of agility and speed. Therefore, this study aims to describe the contribution of agility and speed both individually and together. With the dribbling ability of SSB football players, a studio of learning activities in 2010. The population of the study was 75 football players from the SSB Sanggar Muara Bungo Learning Activities in 2010. Sampling was carried out by means of porpusive sampling, that is, the age group of 17 to 20 years, with 30 people. To achieve the purpose of this study, there were three instruments used, (1) zig-zag run test, to measure agility variable, (2) 50 year (45 meter) running test to measure speed variable, (3) dribbling ability test to measure dribbling ability variable. Data were analyzed with product moment correlation and multiple correlation with the determinant formula. The finding of this study shows; (1) there is a significant relationship between agility and dribbling ability, with the contribution of agility 43.30% to dribbling ability, (2) there is a significant relationship between speed and dribbling ability. Contributions of agility 24.21%, (3) there is a significant relationship between agility and speed together with the ability of dribbling, the contribution of agility and speed to the dribbling ability of 43.59%.